Republic of Montenegro : 2007 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Republic of Montenegro. (IMF Staff Country Reports; Country Report ;, 2008)
The economic expansion in Montenegro is proceeding at full strength. The economy is overheating. Rapid credit growth is overstretching banks, and has contributed to ballooning asset prices. Eroding competitiveness is a concern. Management of the boom falls on fiscal policy. Tax cuts have been procyclical and potentially destabilizing. Fiscal risks need to be contained. The main focus of credit policy should be to strengthen banking sector supervision. Completing the transition to a market economy should be kept at the top of the policy agenda.